Diagnostic Problems and Monitoring Of Diabetes Mellitus In Patients With Aplastic Anemia and Hypoalbuminemia - Gautama M, Putu Gizha Satrya; Saraswati, Made Ratna (CV. Publikasi Indonesia, 2025)
Aplastic anemia is a clinical syndrome that occurs due to bone marrow failure. One of the most common metabolic complications is diabetes mellitus (DM). The emergence of DM allegedly caused by damage of pancreatic β cells due to accumulation of Fe post-transfusion as well as longterm steroid treatment during the patient's care. This case reported a 41-year-old male patient with steroid-resistant aplastic anemia since 8 years ago, exceeding iron, and moderate malnutrition with hypoalbuminemia. He routinely received red blood cell transfusions and steroid therapy. Since 3 months ago the patient felt classic DM symtomps. Initial laboratory examination found there were normochromic normocytic anemia and thrombocytopenia. Hyperglycemia, hypoalbuminemia, high glycated hemoglobin (HbA1C) levels, and normal glycated albumin (GA) levels were also obtained. Patient was diagnosed with DM. He was treated with medical nutrition therapy, red blood cell transfusion, human albumin transfusion, insulin, and his blood glucose were monitored regularly. Monitoring of glycemic control in DM patients is essential since DM is a chronic disease. In this case, the patient’s glycemic control assessment was using a combination of several methods and biomarkers, such as HbA1C, GA, and eAG (fasting glucose and post prandial glucose).